Plasma VWF: Ag levels predict long-term clinical outcomes in patients with acute myocardial infarction - Xier, Zulipiyemu; Zhu, Yu-Xia; Tang, Shou-Wei; Kong, Can; Aili, Dilihumaer; Huojia, Guzailinuer; Peng, Hui (Frontiers in Cardiovascular Medicine, 2023)
Background A vital role in coronary artery disease is played by Von Willebrand factor (VWF), which serves as a bridge between platelets and the subendothelial matrix after vessel damage. The purpose of the study was to assess the validity of plasma VWF antigen (VWF: Ag) levels as a predictor of clinical outcomes after acute myocardial infarction (AMI). Methods Three hundred and seventy-four patients were studied following coronary angiography, including 209 patients suffering from acute myocardial infarction and 165 healthy participants. Coronary angiography was followed by measurement of plasma VWF: Ag levels. Over a 2-year follow-up period, major adverse cardiopulmonary and cerebrovascular events (MACEs) were the primary endpoint. All-cause mortality was investigated as a secondary endpoint. Results When compared to controls, patients with AMI had mean plasma VWF: Ag levels that were 1.63 times higher (0.860 ± 0.309 vs. 0.529 ± 0.258 IU/ml; P < 0.001). The plasma VWF: Ag levels were substantially higher in patients who experienced MACEs after myocardial infarction vs. those without MACEs (1.088 ± 0.253 vs. 0.731 ± 0.252 IU/ml; P < 0.001). For predicting long-term MACEs using the optimal cut-off value (0.7884 IU/ml) of VWF: Ag, ROC curve area for VWF: Ag was 0.847, with a sensitivity of 87.2% and a specificity of 66.3% (95%CI: 0.792–0.902; P = 0.001). Two-year follow-up revealed a strong link between higher plasma VWF: Ag levels and long-term MACEs. At the 2-year follow-up, multivariate regression analysis revealed an independent relationship between plasma VWF: Ag levels and MACEs (HR = 6.004, 95%CI: 2.987–12.070). Conclusion We found evidence that plasma VWF: Ag levels were independent risk factors for AMI. Meanwhile, higher plasma VWF: Ag levels are associated with long-term MACEs in people with AMI.